Heritability of Popping Characteristics in Sorghum Grain. Issue 1 (17th October 2016) - Pugh, N. Ace; Awika, Joseph M.; Rooney, William L.
Abstract : Popped sorghum ( Sorghum bicolor L. Moench) has become popular among niche food consumers. To provide product for this market, producers are usually popping grain from hybrids that were not developed for popping. With selection, the popping quality of sorghum could likely be improved substantially, but the relative effects of genotype, environment, and the heritability of popping‐related traits remain unknown. The objectives of this study were (i) to determine the relative effect of both genotype and environment on popping quality and (ii) to estimate heritability of these traits in sorghum. Using hot‐air popping, popping efficiency and the expansion ratio were evaluated in grain from 130 recombinant inbred lines (Sureño/RTx430) grown in three different Texas environments. Both popping efficiency and the expansion ratio were affected by genotype, environment, and the genotype × environment interaction. Using combined analysis, the heritability on an entry‐mean basis for popping efficiency was 0.674 (0.579 to 0.746) while the expansion ratio was 0.759 (0.687 to 0.811). These results indicate that both the genotype and environment should be carefully selected to optimize popping productivity and quality. Further, the heritability of these traits indicates that selection for improved popping is possible.